Narrative Transportation And Propaganda Language On Nike’s Youtube Channel : A Discourse Analysis - Awerlin Zalukhu; Raflis Raflis (Jurnal Ilmiah Pendidikan Scholastic, 2025)
The title of this research is “Narrative Transportation and Propaganda Language on Nike’s YouTube Channel: a Discourse Analysis.” This research aims to analyzed narrative transportation, propaganda language, and cohesion-coherence contained in Nike advertisement. The research method used is the descriptive qualitative discourse analysis. The research data consists of 17 advertisement videos uploaded on Nike's official YouTube platform during the period July 2024 to February 2025. The analysis was conducted using three theories: Transportation Imagery Model theory by Green & Brock, Appraisal theory by Martin & White, and Cohesion-coherence theory by Halliday & Hasan. The findings shows that Nike advertisement use more narratives that tell the character stories of iconic athletes. The storyline consistently features narratives of struggle, self-doubt, and difficult situations athletes face. The language of propaganda is found through a short theme or tagline that appears at the end of the advertisement video. The theme or tagline is explained through the narrator's expression so that it forms the audience's perception of the values offered by Nike. Cohesion and coherence of the narrative are formed through lexical links, the use of conjunctions, and logical storylines so that the advertisement message can be understood and accepted intact by the audience.